The impact of financial technology on the net income of saudi Islamic banks - Elhouari Mohammed; Mehdaoui Mouataz Biallah Benameur; Benallal Belkacem; Habibi Zineb; Guettaf Mohamed Yoheir (Bankarstvo, 2025)
This research investigates the impact of financial technology on the financial performance of Islamic banks in Saudi Arabia from 2010 to 2023, focusing on four banks that fully adhere to Sharia principles-Al Rajhi, Al Jazeera, Al Bilad, and Al Inma-as a pure model of Islamic banking. We utilized the Panel Quantile Model to analyze and measure the impact of financial technology on net income. The results reveal that an increase in ATMs is associated with higher net income, particularly in smaller banks, while the impact of POS termi-nals is positive for smaller banks but negative for larger ones. Furthermore, the adoption of secondand thirdgeneration technologies negatively affects net income due to high implementation costs. The study emphasizes the importance of evaluating each technology individually to understand its specific impact on financial performance.